Experimental Investigation of a Double Expansion Chamber Reactive Muffler for Stationary Diesel Engine. (October 2014) - Ingle, Ravindra; Jadhav, J.M.; Manvi, V.S.; Sawant, M.A.; Talekar, V.D.
The increasing need to control noise levels in our environment produced by internal combustion engines, demands the accurate designing of mufflers to meet specific noise emission norms. This paper describes a theoretical and experimental study of a circular double expansion chamber reactive muffler designed specifically for a stationary generator engine. For the theoretical approach, the equations are solved by four pole transfer matrix method using MATLAB software to obtain optimized dimensions of three mufflers at desired maximum transmission loss and at frequencies at which highest sound level is observed. MATLAB software is also used to obtain the graphs for transmission loss versus frequency. In the experimental method a white noise 1D plane wave is generated in the impedance tube attached on both sides of the muffler to obtain the transmission loss. The theoretical results obtained are then compared with experimental results for validation. The theoretical results are well correlated with the experimental results.